Sodium bismuth titanate-based oriented multilayer ceramic capacitor and preparation method thereof
Through the preparation method of sodium bismuth titanate-based multi-layer ceramic capacitor, combined with <111>-SrTO3 template and low-speed ball milling technology, the problem of high strain in ceramic capacitors under high electric field is solved, and high energy storage density and Efficient multi-layer ceramic capacitors.
Patent Information
- Application Number
- CN202411584319.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-07
AI Technical Summary
The existing multi-layer ceramic capacitors have a large strain under high applied electric field, which limits the improvement of their energy storage characteristics. The [111] orientation of barium titanate-based textured ceramics is difficult to drive the orientation of the grain of sodium bismuth titanate-based ceramics. Grow.
Using the preparation method of a sodium bismuth titanate-based <111> orientation multilayer ceramic capacitor, by using (1-x)(0.65Na0.5Bi0.5TiO3-0.35Sr0.7Bi0.2TiO3)-xMnO2 ceramic powder and <111>-SrTO3 The template is combined, and casting, warm water isostatic pressure and long-term sintering are performed after low-speed ball milling to ensure the directional growth of ceramic grains along a specific crystallographic direction.
The energy storage density and energy storage efficiency of multi-layer ceramic capacitors under high applied electric fields have been significantly improved, with energy storage density reaching 15.6 J/cm3, energy storage efficiency >90%, and better pulse energy storage performance has been achieved.
Smart Images

Figure CN119400592A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of multilayer ceramic capacitor preparation, and specifically relates to a sodium bismuth titanate-based <111> Oriented multilayer ceramic capacitor and preparation method thereof. Background Art
[0002] One of the keys to achieving high energy storage characteristics of multilayer ceramic capacitors is to be able to withstand high external electric fields. However, large strain under high fields limits further improvement of the energy storage characteristics of multilayer ceramic capacitors. The Chinese patent with publication number: CN117637344 A provides a chemical formula of (1- x )Bi a Na b Sr c-x Ca 1-y La 2y / 3 TiO3, 0.1 ≤ x ≤0.5、0.1≤ y ≤0.9, a + b + c =0.965, 0.2≤ a ≤0.5、0.2≤ b ≤0.5、0≤ c ≤0.3 antiferroelectric dielectric ceramic materials solve the problem of low energy storage density of lead-free dielectric ceramic materials, but the energy storage density of this material is still less than 10 J / cm 3 , and the energy storage efficiency is less than 80%. The texturing process is a key technology for the preparation of multilayer textured ceramics with specific oriented grains of high energy density dielectrics. The strain and electromechanical breakdown probability under strong fields are reduced through grain orientation engineering, so that multilayer ceramic capacitors can withstand higher external electric fields and the energy storage density can be significantly improved. The Chinese patent with the publication number of CN116253563 A provides a solution for preparing
[111] oriented barium calcium titanate lead-free piezoelectric textured ceramics using
[111] oriented flake BaTiO3 template as a directional template, solving the problem that the
[111] oriented BaTiO3 template seed crystal used in barium calcium titanate-based textured ceramics is difficult to prepare, has a small particle size, and has a narrow controllable range. However, the
[111] oriented flake BaTiO3 template cannot drive the directional growth of sodium bismuth titanate-based ceramic grains. The tape casting process is a conventional process for preparing multilayer components. A single-layer ceramic green film strip can be obtained by tape casting, and then the ceramic body stacked with multiple layers of ceramic green film strips can be subjected to warm water isostatic pressing to obtain a green block. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the present invention provides a sodium bismuth titanate-based <111> The preparation method of oriented multilayer ceramic capacitors enables the multilayer ceramic capacitors to withstand higher external electric fields and significantly improve the energy storage density.
[0004] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a sodium bismuth titanate-based <111> A method for preparing an oriented multilayer ceramic capacitor comprises the following steps: (1- x )(0.65Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)- x MnO2, x =0.004-0.006 ceramic powder, surfactant and solvent are added into a ball mill, and the mixture is evenly mixed to obtain material A; Add plasticizer and binder to material A, mix evenly by ball milling, and obtain material B; Add to material B <111> -SrTO3 template, low speed ball milling for 0.5-1h to obtain ceramic slurry; Degassing the ceramic slurry in a vacuum environment to obtain a tape-cast ceramic slurry; Casting the tape-cast ceramic slurry into a film tape; After preparing the inner electrode on the membrane strip, the membrane strip is naturally dried and then cut into membrane sheets of target size; The membranes are stacked layer by layer according to the position of the electrodes, and the electrodes on two adjacent surfaces form interdigitated electrodes; The stacked multilayer membrane is subjected to warm water isostatic pressing at 70-80°C and 20-50MPa for 10-120min. During the warm water isostatic pressing, the pressure is gradually increased to the target pressure at a pressure increase interval of 5MPa, and each pressure point is maintained for at least 5min to obtain a multilayer green body; The multilayer green body is calcined in an air atmosphere to remove organic matter; After the multi-layer green body with organic matter removed is sintered at 1180-1250°C for 20-30 hours, it is cooled to room temperature in the furnace to obtain a multi-layer ceramic; The two ends of the exposed interdigital electrodes of the obtained multilayer ceramic were coated with conductive slurry and kept at 550°C for 30 min to attach the end electrodes to obtain sodium bismuth titanate-based <111> Oriented Multilayer Ceramic Capacitors.
[0005] Furthermore, the (1- x )(0.65Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)- x MnO2, x =0.004~0.006, prepared by solid phase sintering method, with a particle size of 0.8-1μm.
[0006] Furthermore, the added solvent is a mixed solvent of butanone and ethanol in a mass ratio of 1:1, the surfactant is triolein, and the mass ratio of sodium bismuth titanate-based ceramic powder, surfactant and mixed solvent is 32:1:17.
[0007] Furthermore, the added binder is polyvinyl butyral, the plasticizer is dibutyl phthalate, and the mass ratio of the sodium bismuth titanate-based ceramic matrix powder, the binder and the plasticizer is 18:1:1.
[0008] Furthermore, the <111> -SrTO3 template was prepared by molten salt method according to topological chemical reaction, Ba6Ti 17 O 40 The precursor and SrCl2·6H2O were mixed in a molar ratio of 1:12 and calcined at 900℃. <111> -The SrTO3 template thickness is 1.5-2 μm, and the aspect ratio is greater than 10; the rotation speed of the low-speed ball mill is 100-150 r / min.
[0009] Furthermore, when defoaming, no bubbles appear visually on the slurry surface within 5 minutes.
[0010] Furthermore, when the tape-cast ceramic slurry is tape-cast into a film tape, the scraper height of the tape-casting machine is 40-50 μm, and the film tape conveying speed is 15-20 cm / min.
[0011] Furthermore, when calcining to remove organic matter: the sample was placed in a heating furnace, heated from room temperature to 600°C at a heating rate of 0.5°C / min and then kept at this temperature for 5 hours.
[0012] Furthermore, during sintering, the temperature is increased from room temperature to the holding temperature at a heating rate of 1°C / min.
[0013] The present invention also provides a sodium bismuth titanate-based <111> The oriented multilayer ceramic capacitor is obtained by adopting the above preparation method.
[0014] Compared with the prior art, the present invention has at least the following beneficial effects: the sodium bismuth titanate-based <111> Oriented multilayer ceramic capacitors can achieve an energy storage density of 15.6 J / cm at an electric field of 840 kV / cm 3 , energy storage efficiency>90%, the applied electric field is significantly improved, and better pulse energy storage performance can be achieved under high applied electric field; low-speed ball milling can ensure that the template is uniformly dispersed in the ceramic slurry without breaking the template; long-term sintering and heat preservation can make the grains of the green block with the template added grow in a specific crystallographic direction. The preparation method of the present invention is simple and easy to operate, has low equipment requirements, easy to control reaction conditions, and good repeatability.
[0015] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 This is a schematic diagram of the preparation method in Example 1; Figure 2 0.995 (0.65 Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)-0.005MnO2 ceramic powder and <111> -SrTO3 template with a mass ratio of 20:1 <111> Room temperature hysteresis loop of oriented multilayer ceramic capacitors under 840kV / cm electric field, energy storage density and energy storage efficiency diagrams under different electric field strengths; Figure 3 0.996 (0.65 Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)-0.004MnO2 ceramic powder and <111> -SrTO3 template with a mass ratio of 10:1 <111> Room temperature hysteresis loop of oriented multilayer ceramic capacitors under 840 kV / cm electric field, and energy storage density and energy storage efficiency diagrams under different electric field strengths.
[0017] Figure 4 0.994 (0.65 Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)-0.006MnO2 ceramic powder and <111> -SrTO3 template with a mass ratio of 10:1 <111> Room temperature hysteresis loop of oriented multilayer ceramic capacitors under 840 kV / cm electric field, and energy storage density and energy storage efficiency diagrams under different electric field strengths. DETAILED DESCRIPTION
[0018] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0019] Example 1 Preparation of a sodium bismuth titanate-based <111> Oriented multilayer ceramic capacitors, the specific method is as follows: (1) 0.995 (0.65 Na) with a particle size of about 1 μm prepared by solid phase sintering 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)-0.005MnO2 ceramic powder and triolein surfactant, a mixed solvent of ethanol and butanone in a mass ratio of 1:1 are added to a ball mill in a mass ratio of 32:1:17. The ball mill contains zirconium oxide balls with a diameter of 10 mm and a diameter of 5 mm in a number ratio of 2:3. The volume ratio of zirconium oxide balls to the chemical reagents in the ball mill is 3:2. The speed of ball milling is 300r / min, and the ball milling is performed for 24h to obtain material A; (2) After the first ball milling, add polyvinyl butyral binder and dibutyl phthalate plasticizer into the ball mill, 0.995 (0.65 Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 The mass ratio of TiO3)-0.005MnO2 ceramic powder, binder and plasticizer is 18:1:1, and the ball milling is continued for 24 h to obtain material B. (3) Ba6Ti prepared by molten salt method 17 O 40 The precursor and SrCl2·6H2O were mixed in a molar ratio of 1:12 and calcined at 900 °C to obtain a film with an aspect ratio greater than 10 and a thickness of 1.5-2 μm. <111> -SrTO3 template, <111> -SrTO3 template was added to the ball mill, 0.995 (0.65Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2TiO3)-0.005MnO2 ceramic powder and <111> -SrTO3 template had a mass ratio of 20:1 and was ball milled at a low speed of 100 r / min for 1 h; (4) placing the slurry obtained in step (3) in a dry beaker and placing it in a defoamer for defoaming for 1 h; (5) Casting the slurry after degassing in step (4) into a film tape on a casting machine, setting the scraper height of the casting machine to 40 μm, setting the film tape conveying speed to 15 cm / min, and leaving it at room temperature for 24 h; (6) Printing platinum electrodes on the membrane using a screen printing mold and then letting it dry naturally; (7) Cutting the membrane strip obtained in step (6) into square membrane sheets of 25 cm × 25 cm using a cutting machine; (8) laminating the membrane obtained in step (7) according to the position of the electrodes, so that two adjacent inner electrodes are interdigitated electrodes with partial areas offset; (9) The laminated sample obtained in step (8) is subjected to warm water isostatic pressing. The water temperature is kept constant at 75°C before the sample is placed. During the warm water isostatic pressing, the pressure is gradually increased to 30 MPa at an interval of 5 MPa, and each pressure point is maintained for 10 min; (10) calcining the sample obtained in step (9) in an air atmosphere to remove organic matter, placing the sample in a muffle furnace, heating it from room temperature to 600°C at a heating rate of 0.5°C / min, and then keeping it at that temperature for 5 h; (11) The sample obtained after the treatment in step (10) was sintered at 1180°C. The sample was placed in a muffle furnace and heated from room temperature to 1180°C at a heating rate of 1°C / min, then kept at this temperature for 30 h, and then cooled to room temperature in the furnace; (12) The two ends of the bare interdigitated electrodes of the sample obtained in step (11) were coated with conductive slurry, and the samples were kept at 550°C for 30 min to attach the end electrodes, thereby obtaining a sodium bismuth titanate-based <111> Oriented Multilayer Ceramic Capacitors.
[0020] 0.995 (0.65 Na) prepared in Test Example 1 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)-0.005MnO2 components <111> Room temperature hysteresis loops of oriented multilayer ceramic capacitors were plotted and the energy storage density and efficiency were calculated.
[0021] 0.995 (0.65 Na) prepared in Example 1 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi0.2 TiO3)-0.005MnO2 components <111> The room temperature hysteresis loop of oriented multilayer ceramic capacitors, the test results of energy storage density and energy storage efficiency under different electric fields are shown in Figure 2. Figure 2 As shown. Figure 2 It can be seen that the room temperature hysteresis loop under an electric field of 840 kV / cm is a typical hysteresis loop shape of a relaxor ferroelectric, and the hysteresis of the hysteresis loop is small. The energy storage density under an electric field of 840 kV / cm reaches 15.6 J / cm 3 , the energy storage efficiency is between 93.8% and 95.2%.
[0022] Example 2 Preparation of a sodium bismuth titanate-based <111> Oriented multilayer ceramic capacitors, the specific method is as follows: (1) 0.996 (0.65 Na) with a particle size of about 1 μm prepared by solid phase sintering 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)-0.004MnO2 ceramic powder and triolein surfactant, a mixed solvent of ethanol and butanone in a mass ratio of 1:1 in a ratio of 32:1:17 were added to a ball mill, which contained zirconium oxide balls with a diameter of 10 mm and a diameter of 5 mm in a ratio of 2:3, and the volume ratio of zirconium oxide balls to the chemical reagents in the ball mill was 3:2. The speed of ball milling was 300 r / min, and the ball milling was performed for 15 hours to obtain material A; (2) After the first ball milling, add polyvinyl butyral binder and dibutyl phthalate plasticizer into the ball mill, 0.996 (0.65 Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 The mass ratio of TiO3)-0.004MnO2 ceramic powder, binder and plasticizer is 18:1:1, and the ball milling is continued for 15 h to obtain material B; (3) Ba6Ti prepared by molten salt method 17 O 40 The precursor and SrCl2·6H2O were mixed in a molar ratio of 1:12 and calcined at 900 °C to obtain a 1.5-2 μm thick film with an aspect ratio greater than 10. <111> -SrTO3 template, <111> -SrTO3 template was added to the ball mill, 0.996 (0.65Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2TiO3)-0.004MnO2 ceramic powder and <111> -SrTO3 template had a mass ratio of 10:1 and was ball milled at a low speed of 150 r / min for 1 h; (4) placing the slurry obtained in step (3) in a dry beaker and placing it in a defoamer for defoaming for 1 h; (5) Casting the defoamed slurry in step (4) into a film tape on a casting machine, with the scraper height of the casting machine set to 40 μm and the film tape conveying speed set to 15 cm / min, and leaving it at room temperature for 12 h; (6) Printing platinum electrodes on the membrane using a screen printing mold and then letting it dry naturally; (7) Cutting the membrane strip obtained in step (6) into square membrane sheets of 25 cm × 25 cm using a cutting machine; (8) laminating the membrane obtained in step (7) according to the position of the electrodes, so that two adjacent inner electrodes are interdigitated electrodes with partial areas offset; (9) The laminated sample obtained in step (8) is subjected to warm water isostatic pressing. The water temperature is kept constant at 75°C before the sample is placed. During the warm water isostatic pressing, the pressure is gradually increased to 50 MPa at an interval of 5 MPa, and each pressure point is maintained for 5 min; (10) calcining the sample obtained in step (9) in an air atmosphere to remove organic matter, placing the sample in a muffle furnace, heating it from room temperature to 600°C at a heating rate of 0.5°C / min, and then keeping it at that temperature for 5 h; (11) The sample obtained after the treatment in step (10) was sintered at 1200°C. The sample was placed in a muffle furnace and heated from room temperature to 1200°C at a heating rate of 0.5°C / min, then kept at this temperature for 25 h, and then cooled to room temperature in the furnace; (12) Apply conductive paste to both ends of the bare interdigitated electrodes of the sample obtained in step (11), and heat at 575 °C for 10 min to attach the end electrodes to obtain sodium bismuth titanate-based <111> Oriented Multilayer Ceramic Capacitors.
[0023] 0.996 (0.65 Na) prepared in Test Example 2 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)-0.004MnO2 components <111> Room temperature hysteresis loops of oriented multilayer ceramic capacitors were plotted and the energy storage density and efficiency were calculated.
[0024] 0.996 (0.65 Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi0.2 TiO3)-0.004MnO2 components <111> The room temperature hysteresis loop of oriented multilayer ceramic capacitors, the test results of energy storage density and energy storage efficiency under different electric fields are shown in Figure 2. Figure 3 As shown. The sodium bismuth titanate-based <111> The room temperature hysteresis loop shape and properties of the oriented multilayer ceramic capacitor are similar to those of the capacitor prepared in Example 1. <111> Oriented multilayer ceramic capacitors, with an energy storage density of 15.3 J / cm at an electric field of 840 kV / cm 3 , the energy storage efficiency is between 94.1% and 95.1%.
[0025] Example 3 Preparation of a sodium bismuth titanate-based <111> Oriented multilayer ceramic capacitors, the specific method is as follows: (1) 0.994 (0.65 Na) with a particle size of about 1 μm prepared by solid phase sintering 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)-0.006MnO2 ceramic powder and triolein surfactant, a mixed solvent of ethanol and butanone in a mass ratio of 1:1 were added to a ball mill in a mass ratio of 32:1:17, and there were zirconium oxide balls with a diameter of 10 mm and a diameter of 5 mm in a number ratio of 2:3, and the volume ratio of zirconium oxide balls to the chemical reagents in the ball mill was 3:2. The speed of ball milling was 300 r / min, and the ball milling was performed for 24 hours to obtain material A; (2) After the first ball milling, polyvinyl butyral binder and dibutyl phthalate plasticizer were added to the ball mill, 0.994 (0.65 Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 The mass ratio of TiO3)-0.006MnO2 ceramic powder, binder and plasticizer was 18:1:1, and the ball milling was continued for 15 h; (3) Ba6Ti prepared by molten salt method 17 O 40 The precursor and SrCl2·6H2O were mixed in a molar ratio of 1:12 and calcined at 900 °C to obtain a 1.5-2 μm thick film with an aspect ratio greater than 10. <111> -SrTO3 template, <111> -SrTO3 template was added to the ball mill, 0.994 (0.65Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2TiO3)-0.006MnO2 ceramic powder and <111> -SrTO3 template had a mass ratio of 10:1 and was ball milled at a low speed of 130 r / min for 1 h; (4) placing the slurry obtained in step (3) in a dry beaker and placing it in a defoamer for defoaming for 1 h; (5) Casting the slurry after degassing in step (4) into a film tape on a casting machine, setting the scraper height of the casting machine to 40 μm, setting the film tape conveying speed to 15 cm / min, and leaving it at room temperature for 20 h; (6) Printing platinum electrodes on the membrane using a screen printing mold and then letting it dry naturally; (7) Cutting the membrane strip obtained in step (6) into square membrane sheets of 25 cm × 25 cm using a cutting machine; (8) laminating the membrane obtained in step (7) according to the position of the electrodes, so that two adjacent inner electrodes are interdigitated electrodes with partial areas offset; (9) The laminated sample obtained in step (8) is subjected to warm water isostatic pressing. The water temperature is kept constant at 80°C before the sample is placed. During the warm water isostatic pressing, the pressure is gradually increased to 45 MPa at an interval of 5 MPa, and each pressure point is maintained for 5 min; (10) calcining the sample obtained in step (9) in an air atmosphere to remove organic matter, placing the sample in a muffle furnace, heating it from room temperature to 600°C at a heating rate of 0.5°C / min, and then keeping it at that temperature for 5 h; (11) The sample obtained after the treatment in step (10) was sintered at 1250°C. The sample was placed in a muffle furnace and heated from room temperature to 1250°C at a heating rate of 0.5°C / min, then kept at this temperature for 20 h, and then cooled to room temperature in the furnace; (12) The two ends of the bare interdigitated electrodes of the sample obtained in step (11) were coated with conductive slurry, and the samples were kept at 600 °C for 10 min to attach the end electrodes, thereby obtaining a sodium bismuth titanate-based <111> Oriented Multilayer Ceramic Capacitors.
[0026] 0.994 (0.65 Na) prepared in Test Example 3 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)-0.006MnO2 components <111> Room temperature hysteresis loops of oriented multilayer ceramic capacitors were plotted and the energy storage density and efficiency were calculated.
[0027] 0.994 (0.65 Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi0.2 TiO3)-0.006MnO2 components <111> The room temperature hysteresis loop of oriented multilayer ceramic capacitors, the test results of energy storage density and energy storage efficiency under different electric fields are shown in Figure 2. Figure 4 As shown. The sodium bismuth titanate prepared in Example 3 <111> The room temperature hysteresis loop shape and properties of the oriented multilayer ceramic capacitor are similar to those of the capacitors prepared in Examples 1 and 2. <111> Oriented multilayer ceramic capacitors, with an energy storage density of 15.1 J / cm at an electric field of 840 kV / cm 3 The energy storage efficiency is 94.0%-95.2%. The reason is that the electrostriction of perovskite ceramics has strong anisotropy, which <111> The electrostrictive strain of the multilayer ceramic capacitor can be greatly reduced by arranging the ceramic in the crystallographic direction, thereby avoiding the problem that the large tensile strain induces serious microcracks inside the ceramic and reduces the breakdown electric field. <111> Oriented multilayer ceramic capacitors can further enhance the energy storage performance under high electric field by increasing the applied electric field of sodium bismuth titanate-based ceramics.
[0028] In addition, the present invention adds <111> -SrTO3 template after low-speed ball milling can ensure that the template is uniformly dispersed in the ceramic slurry without breaking the template; long-term sintering and heat preservation can make the grains of the green block with the template added grow in a specific crystallographic direction; the preparation method of the present invention has the characteristics of simple operation and low equipment requirements, can ensure that the product has high energy storage performance, and the reaction conditions of the entire preparation method are easy to control and have good repeatability.
[0029] In summary, the present invention provides a sodium bismuth titanate-based <111> A method for preparing an oriented multilayer ceramic capacitor comprises the following steps: x )(0.65Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)- x MnO2, x=0.004-0.006 Ceramic powder, surfactant and solvent are added to a ball mill, and the mixture is evenly mixed to obtain material A; plasticizer and binder are added to material A, and the mixture is evenly mixed to obtain material B; and <111> -SrTO3 template, low-speed ball milling for 0.5-1h to obtain ceramic slurry; degas the ceramic slurry in a vacuum environment to obtain cast ceramic slurry; cast the cast ceramic slurry into a film strip; prepare the inner electrode on the film strip and naturally dry it before cutting it into a film of target size; stack the film layers layer by layer according to the position of the electrode, and the electrodes on the two adjacent surfaces form interdigitated electrodes; the stacked multilayer film is isostatically pressed in warm water at 70-80℃ and 20-50MPa for 10-120min, and during the warm water isostatic pressing, gradually increase the pressure to the target pressure with a pressure increase interval of 5MPa, and each pressure point is maintained for at least 5 min to obtain a multilayer green body; calcining the multilayer green body in an air atmosphere to remove organic matter; sintering the multilayer green body with organic matter removed at 1180-1250°C for 20-30 hours, cooling to room temperature with the furnace to obtain a multilayer ceramic; brushing a conductive slurry on both ends of the exposed interdigitated electrodes of the obtained multilayer ceramic, and keeping the temperature at 550-600°C for 30 min to attach the end electrodes to obtain a sodium bismuth titanate-based <111> Oriented multilayer ceramic capacitors. This method uses a low-speed ball milling dispersion template and a tape casting process to obtain a single-layer ceramic green film strip, combines screen printing to prepare an interdigitated internal electrode, and laminates multiple layers of green film strips with printed internal electrodes, performs warm water isostatic pressing, and sintering for a long time to prepare a sodium bismuth titanate-based <111> Oriented multilayer ceramic capacitors. Low-speed ball milling can ensure that the template is evenly dispersed in the ceramic slurry without breaking the template. Long-term sintering and heat preservation can make the grains of the green block with the template added grow in a specific crystallographic direction. Compared with sodium bismuth titanate-based multilayer ceramic capacitors, the orientation of ceramic grains is <111> The crystallographic direction is arranged, and the applied electric field is significantly increased, and a better pulse energy storage performance can be achieved under a high applied electric field. This method can not only reduce the process steps, save process costs, and improve the density of the capacitor, but also significantly improve the applied electric field and energy storage density of the capacitor.
[0030] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A sodium bismuth titanate-based <111> A method for preparing an oriented multilayer ceramic capacitor, characterized in that: The following steps are involved: (1- x )(0.65Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)- x MnO2, x =0.004-0.006 ceramic powder, surfactant and solvent are added into a ball mill, and the mixture is evenly mixed to obtain material A; Add plasticizer and binder to material A, mix evenly by ball milling, and obtain material B; Add to material B <111> -SrTO3 template, low speed ball milling for 0.5-1h to obtain ceramic slurry; Degassing the ceramic slurry in a vacuum environment to obtain a tape-cast ceramic slurry; Casting the tape-cast ceramic slurry into a film tape; After preparing the inner electrode on the membrane strip, the membrane strip is naturally dried and then cut into membrane sheets of target size; The membranes are stacked layer by layer according to the position of the electrodes, and the electrodes on two adjacent surfaces form interdigitated electrodes; The stacked multilayer membrane is subjected to warm water isostatic pressing at 70-80°C and 20-50MPa for 10-120min. During the warm water isostatic pressing, the pressure is gradually increased to the target pressure at a pressure increase interval of 5MPa, and each pressure point is maintained for at least 5min to obtain a multilayer green body; The multilayer green body is calcined in an air atmosphere to remove organic matter; After the multi-layer green body with organic matter removed is sintered at 1180-1250°C for 20-30 hours, it is cooled to room temperature in the furnace to obtain a multi-layer ceramic; The two ends of the exposed interdigital electrodes of the obtained multilayer ceramic were coated with conductive slurry and kept at 550-600°C for 30 min to attach the end electrodes to obtain sodium bismuth titanate-based <111> Oriented Multilayer Ceramic Capacitors.
2. The preparation method according to claim 1, characterized in that: The (1- x )(0.65Na 0.5 Bi 0.5 TiO3-0.35Sr 0.7 Bi 0.2 TiO3)- x MnO2, x =0.004~0.006, prepared by solid phase sintering method, with a particle size of 0.8-1μm.
3. The preparation method according to claim 1, characterized in that: The added solvent is a mixed solvent of butanone and ethanol in a mass ratio of 1:1, the surfactant is triolein, and the mass ratio of the sodium bismuth titanate-based ceramic powder, the surfactant and the mixed solvent is 32:1:
17.
4. The preparation method according to claim 1, characterized in that: The added binder is polyvinyl butyral, the plasticizer is dibutyl phthalate, and the mass ratio of sodium bismuth titanate-based ceramic matrix powder, the binder and the plasticizer is 18:1:
1.
5. The preparation method according to claim 1, characterized in that: Said <111> -SrTO3 template was prepared by molten salt method according to topological chemical reaction, Ba6Ti 17 O 40 The precursor and SrCl2·6H2O were mixed in a molar ratio of 1:12 and calcined at 900℃. <111> -SrTO3 template thickness is 1.5-2μm, and aspect ratio is greater than 10; the rotation speed of low-speed ball milling is 100-150 r / min.
6. The preparation method according to claim 1, characterized in that: When defoaming, remove bubbles until no bubbles appear visually on the slurry surface within 5 minutes.
7. The preparation method according to claim 1, characterized in that: When the cast ceramic slurry is cast into a film tape, the scraper height of the casting machine is 40-50 μm, and the film tape conveying speed is 15-20 cm / min.
8. The preparation method according to claim 1, characterized in that: The specific method of calcination to remove organic matter is: place the sample in a muffle furnace, heat it from room temperature to 600 °C at a heating rate of 0.5 °C / min, and then keep it at this temperature for 5 h.
9. The preparation method according to claim 1, characterized in that: During sintering, the temperature was increased from room temperature to the holding temperature at a heating rate of 1 °C / min.
10. A sodium bismuth titanate-based <111> An oriented multilayer ceramic capacitor, characterized in that The method is adopted to obtain the product according to any one of claims 1 to 9.
Citation Information
Patent Citations
[111] oriented barium calcium titanate lead-free piezoelectric textured ceramic and preparation method thereof
CN116253563A
Dielectric ceramic material, dielectric ceramic layer, preparation method of dielectric ceramic material and dielectric ceramic layer, and capacitor
CN117637344A